ANALISIS SIKAP AKSEPTOR RID TERHADAP EFEKTIFITAS DAN RESIKO PENGGUNAAN ALAT KONTRASEPSI IUD DIBANDINGKAN SUNTIK KB DAN PIL KB (Studi Kasus pada Pengguna Alat Kontrasepsi 11 D di Desa Tahunan) - Bening Kristyassari (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractThis research aim to analyse acceptor attitude oflUD to usage of in frau ferine device of IVD itself compared to other intrauterine device, that is Injecting KB and Pill of KB. Where the attitude analysis pursuant to risk and efektifilas. Population at this research is entire acceptor mothers of IUD in Tahunan Jepara. Technique Intake by simple sampling random with amount of taken sampel counted 92 responder. Data type is primary' data and sekunder data collected with kuesioner, documentation and intennew. Analysis technique is Friedman Test, that is different test for related sampel more than two criterion.Pursuant to data analysis, first conclusion the obtained is mean perception of acceptor attitude of IUD to efektifitas usage of intrauterine device of IUD compared to other intrauterine device ha\>e difference. Sequence intrauterine device pursuant to efektifitas, started from most effective is IUD, Inject KB and Pill of KB. Conclusion both, mean perception of acceptor attitude of IUD to risk usage of intrauterine device of IUD compared to other intrauterine device [do] not have difference Intrauterine de\>ice owning highest risk is Injecting KB. IUD and is last of Pill of KB. Keyword; consumer attitude, intrauterine device affectivity, intrauterine dexice risk, IUD, Inject KB and Pill of KB.